The legal and socioeconomic challenges for environmental protection in marine policy and the silk route maritime - Muhammad Bilawal Khaskheli; Yincheng Li; Yongchen Zhao; Wang Shumin (Frontiers in Marine Science, 2025)
IntroductionThe intersection of legal frameworks and socioeconomic interests poses a significant challenge to ocean policy focused on environmental protection. This article examines the complexities of international regulation, national interests, and local needs. Legal frameworks like the United Nations Convention on the Law of the Sea provide a foundation for sustainable use and environmental protection. However, the implementation of these frameworks varies significantly around the world. Socioeconomic disparities and their impact on governance and resource management further undermine resource utilization and contribute to environmental degradation. The research compares and contrasts the environmental laws of various countries and examines the laws of nations under the United Nations’ global governance. MethodsThis paper’s research approach adopts a literature review with secondary data from official databases, such as UNCLOS, the United Nations, and other official databases. We also utilize the consequences of recently published papers in high-impact publishers such as Frontiers, Oxford University Press, Springer, Elsevier, IEEE, Wiley, Taylor & Francis, and MDPI. For cross-border cooperation, there are possibilities and pitfalls of harmonizing monitoring and enforcement of policy. ResultsIt has six tables and three figures that provide statistics reflecting global performance in marine and environmental law, designed to protect the world. DiscussionTherefore, the Belt and Road Initiative and the China-Pakistan Economic Corridor must tackle these issues through collaborative efforts that engage coastal governance participation. Effective ocean governance within these frameworks can encourage regional cooperation, ensuring legal commitments align with socioeconomic realities. Ultimately, it is crucial to maintain a balance that supports marine conservation and sustainable development. Adaptive management strategies and institutional collaboration are needed to pursue these complexities, develop sustainability and resilience in marine ecosystems, and inform more effective environmental protection policies.